2013
DOI: 10.4049/jimmunol.1202493
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Is Characterized by Stage-Specific Alterations in DNA Methylation That Occur Early during Myelomagenesis

Abstract: Epigenetic changes play important roles in carcinogenesis and influence initial steps in neoplastic transformation by altering genome stability and regulating gene expression. To characterize epigenomic changes during the transformation of normal plasma cells to myeloma, we modified the HELP assay to work with small numbers of purified primary marrow plasma cells. The nano-HELP assay was used to analyze the methylome of CD138+ cells from 56 subjects representing premalignant (MGUS), early and advanced stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 39 publications
4
77
2
Order By: Relevance
“…To this end, we developed a technique that enabled us to characterize DNA cytosine methylation from prospectively isolated highly enriched human HSC from single individuals in small numbers. We coupled prospective isolation of human HSPC with a modified HELP assay, the so-called nanoHELP (22)(23)(24)(25)(26). We found that most DNA cytosines in human LTHSC, STHSC, CMP, and MEP were methylated, in agreement with findings in other vertebrate somatic stem cells and differentiated tissues (5)(6)(7)54).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To this end, we developed a technique that enabled us to characterize DNA cytosine methylation from prospectively isolated highly enriched human HSC from single individuals in small numbers. We coupled prospective isolation of human HSPC with a modified HELP assay, the so-called nanoHELP (22)(23)(24)(25)(26). We found that most DNA cytosines in human LTHSC, STHSC, CMP, and MEP were methylated, in agreement with findings in other vertebrate somatic stem cells and differentiated tissues (5)(6)(7)54).…”
Section: Discussionsupporting
confidence: 71%
“…The epigenetic signature is enriched for binding sites of known hematopoietic transcription factors and microRNA loci. combining 8-parameter high-speed FACS of primary human BM cells with an optimized nano HpaII-tiny-fragment-enrichment-byligation-mediated-PCR (nanoHELP) (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/ JCI71264DS1) assay (22)(23)(24)(25)(26). This approach permitted examination of single individuals' stem cells isolated as biological replicates, i.e., without pooling of samples prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We further showed that stage 4S-specific hyper-and hypomethylated promoters are located on specific chromosomal locations. Non-random chromosomal distribution of regions differentially methylated between tumor and normal samples, 20,21 and between different tumor stages, 21,22 has been previously reported for other cancer types. In this study, we show that specific chromosomal cytogenetic bands are enriched in stage 4S differentially methylated promoters and, most importantly, that stage 4S tumors show characteristic hypermethylation of specific subtelomeric promoters.…”
Section: Discussionmentioning
confidence: 61%
“…8 We and others have previously speculated that hypomethylation of the highly repetitive elements that make up the 1q12 pericentromeric region may be related to the origin and progression of CNAs of 1q21, [8][9][10] suggesting epigenetic factors are involved. In fact, methylation studies in multiple myeloma (MM) have shown a gradual progression from overall global hypomethylation to DNA hypermethylation of specific genes [11][12][13] and that hypomethylation of repetitive elements may contribute to tumor progression and genomic instability. 14,15 It has previously been demonstrated that hypomethylation of the pericentromeric regions of metaphase chromosomes by 5-azacytidine can induce 1q12 chromosome decondensation 16,17 and somatic associations in chromosome regions 1, 9, and 16 in human lymphocytes.…”
Section: Introductionmentioning
confidence: 99%